ANALISIS KONSEP HERMENEUTIKA DALAM TAFSIR ALQURAN - Muchtar, M. Ilham (Hunafa: Jurnal Studia Islamika, 2016)
The Quran is the holy book has been and will always be interpreted over time. Along with the times, today introduced methods of hermeneutics as an alternative instrument to uncover the meaning behind the text of a verse. Hermeneutics, as a method of interpretation, not only looked at text, but also trying to explore the content of its literal sense. Hermeneutics trying to dig meaning by considering the horizons surrounding the text, either horizon authors, readers horizon, and horizon of the text itself. Application of the concept of hermeneutics in interpreting the Quran is againts to the general rules of Islam, hermeneutics relativize boundaries between verses muhkam and mutasyÄbih, usÅ«l and furu, qaá¹Ä«yah and áºanÄ«yah. Will lead to the deconstruction of the concept of revelation are protected lafadz and meaning. Using the methods of hermeneutics to explain Alquran categorized turned away from the Quran